Impact of phytosterols on liver and distal colon metabolome in experimental murine colitis model: an explorative study. (1st January 2019) - Iaccarino, Nunzia; Amato, Jussara; Pagano, Bruno; Di Porzio, Anna; Micucci, Matteo; Bolelli, Luca; Aldini, Rita; Novellino, Ettore; Budriesi, Roberta; Randazzo, Antonio
Abstract: Phytosterols are known to reduce plasma cholesterol levels and thereby reduce cardiovascular risk. Studies conducted on human and animal models have demonstrated that these compounds have also anti-inflammatory effects. Recently, an experimental colitis model (dextran sulphate sodium-induced) has shown that pre-treatment with phytosterols decreases infiltration of inflammatory cells and accelerates mucosal healing. This study aims to understand the mechanism underlying the colitis by analysing the end-products of the metabolism in distal colon and liver excised from the same mice used in the previous work. In particular, an unsupervised gas chromatography-mass spectrometry (GC-MS) and NMR based metabolomics approach was employed to identify the metabolic pathways perturbed by the dextran sodium sulphate (DSS) insult (i.e. Krebs cycle, carbohydrate, amino acids, and nucleotide metabolism). Interestingly, phytosterols were able to restore the homeostatic equilibrium of the hepatic and colonic metabolome.